Rationally designed helix-turn-helix proteins and their conformational changes upon DNA binding. - Percipalle, P (1995)
Circular dichroism and electrophoretic mobility shift studies were performed to confirm that dimerized N-terminal domains of bacterial repressors containing helix-turn-helix motifs are capable of high-affinity and specific DNA recognition as opposed to the monomeric N-terminal domains. Specific, high-affinity DNA binding proteins were designed and produced in which two copies of the N-terminal 1-62 domain of the bacteriophage 434 repressor are connected either in a dyad-symmetric fashion, with a synthetic linker attached to the C-termini, or as direct sequence repeats. Both molecules bound to their presumptive cognate nearly as tightly as does the natural (full-length and non-covalently dimerized) 434 repressor, showing that covalent dimerization can be used to greatly enhance the binding activity of individual protein segments. Circular dichroism spectroscopy showed a pronounced increase in the alpha-helix content when these new proteins interacted with their cognate DNA and a similar, although 30% lower, increase was also seen upon their interaction with non-cognate DNA. These results imply that a gradual conformational change may occur when helix-turn-helix motifs bind to DNA, and that a scanning mechanism is just as plausible for this motif class as that which is proposed for the more flexible basic-leucine zipper and basic-helix-loop-helix motifs.